Identification of Aquifers Distribution using Geoelectric-Resistivity Method with Schlumberger Configuration in Gedangan Village, Malang Regency - Ahmad N. Faris; Daeng A. Suaidi; Sutrisno Sutrisno; Muhammad Fathur Rouf Hasan; Agung B. Broto (Natural B, Journal of Health and Environmental Sciences, 2019)
Drought is one of the problems in Gedangan Village during the dry season. So that district needs more groundwater resources. The geoelectric-resistivity method usually used for groundwater exploration. This method used for identifying changes in the resistivity of rock layers beneath the earth's surface by flowing direct current (DC). This research intends to identify the pattern of groundwater distribution using the geoelectric-resistivity method with Schlumberger configuration in Gedangan Village, Gedangan District, Malang Regency. Thirteen VES points were obtained by Schlumberger configuration and each long stretch until 400 m. Then each the two parallel VES points arranged to obtain a 2D cross-section. The results indicate this area surrounded by karst and it has lithology consists of sandy marlstone, claystone, and limestone. The resistivity value is between 1.41 - 8.28 Ωm identified as sandy marlstone and it presumed as an aquifer. The aquifers with large amounts of groundwater are in the VES point lines of 01-02, 03-04 and 04-05. These lines are located in the south of the Gedangan district office and the police station.